2016
DOI: 10.1200/jop.2015.007757
|View full text |Cite
|
Sign up to set email alerts
|

Readmissions After Colon Cancer Surgery: Does It Matter Where Patients Are Readmitted?

Abstract: QUESTION ASKED: Do mortality and cost differ for patients with cancer who get readmitted to the hospital within 30 days after their initial cancer surgery on the basis of whether they are admitted to the same hospital where they had their surgery or to a different hospital?SUMMARY ANSWER: Patients with colon cancer who had a 30-day readmission to a different hospital than the one where they received their cancer surgery did not experience higher all-cause mortality, colon cancer-specific mortality, or costs co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…18,19,22,23,30,31 Overall, 11 studies looked at mortality following a fragmented postoperative readmission, and 7 of these included cancer-related surgeries. Among the 5 studies that included only patients with cancer, 15,25,[30][31][32] 3 showed post-operative fragmentation associated with 18% to fivefold higher mortality odds (AOR 1.18-5.66). In 4 studies that included both cancer-related and non-cancer-related surgeries, 19,20,26,27 only 2 found post-operative care fragmentation was associated with increased odds of mortality, but the increase was notable: 50 to 75% higher mortality odds (OR 1.57-1.75).…”
Section: Mortalitymentioning
confidence: 99%
“…18,19,22,23,30,31 Overall, 11 studies looked at mortality following a fragmented postoperative readmission, and 7 of these included cancer-related surgeries. Among the 5 studies that included only patients with cancer, 15,25,[30][31][32] 3 showed post-operative fragmentation associated with 18% to fivefold higher mortality odds (AOR 1.18-5.66). In 4 studies that included both cancer-related and non-cancer-related surgeries, 19,20,26,27 only 2 found post-operative care fragmentation was associated with increased odds of mortality, but the increase was notable: 50 to 75% higher mortality odds (OR 1.57-1.75).…”
Section: Mortalitymentioning
confidence: 99%
“…This could increase patients’ compliance with their health care regimen, which can lead to a reduced number of hospital admissions [ 71 ]. As the risk of rehospitalization is high during the first weeks at home (30% for patients with HF [ 72 ] and 15% for patients treated for CRC) within the first 30 days after discharge [ 73 ], the transition period from hospital to home seems to be an appropriate time to offer digital follow-up care to patients with long-term illnesses such as HF or CRC.…”
Section: Discussionmentioning
confidence: 99%